Functional and Structural Architectures of Allocentric and Egocentric Spatial Coding in Aging: A Combined DTI and fMRI Study - Derbie, Abiot Y.; Chau, Bolton K. H.; Chan, Chetwyn C. H. (Frontiers in Neurology, 2022)
Background Ageing disrupts the optimal balance between neural nodes underlying orienting and attention control functions. Previous studies have suggested that age-related changes in cognitive process are associated to the changes in the myelinated fibre bundles, which affected the speed and actions of the signal propagation across different neural networks. However, whether age-related difference in allocentric and egocentric spatial coding is accounted by the difference in white-matter integrity is unclear. In this study, using DTI and fMRI, we sought to elucidate whether age-related differences in white matter integrity accounts for the difference in nodes to the distributed spatial coding -relevant brain networks. Material and Method Older (n = 24) and younger (n = 27) participants completed the structural (DTI) and fMRI scans during which they engaged in a cue-to-target task to elicit allocentric or egocentric processes. Results and Conclusion Efficient modulation of both allocentric and egocentric spatial coding in fronto-parietal attention network (FPAN) requires structure-function interaction. Allocentric task-modulated connectivity of the fronto-parietal network (FPN) and dorsal attention network (DAN) with the temporal lobe was influenced by the ageing differences of the white-matter tracts of the posterior and superior corona radiata (PCR and SCR), respectively. On the other hand, ageing difference of the superior longitudinal fasciculus mainly influenced the egocentric-task modulated connections of the DAN and FPN with frontal regions and posterior cingulate cortex. This study suggested that functional connections of the FPAN with near and far task-relevant nodes vary significantly with age and conditions.